PENGARUH KOMUNIKASI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. CAHYA PRINTING BALI - Ni Luh Marlina Puspita Sari; I Ketut Setia Sapta; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The company expects good performance from each employee in carrying out the tasks assigned by the company. If the individual in the HR office can run effectively, the company will continue to run effectively. Employee performance plays an important role in an organization. This also happens to CV. Cahya Printing Bali, therefore this study aims to determine the Effect of Communication and Work Experience on Employee Performance on CV. Cahya Printing Bali. The population of this study were all employees of CV. Cahya Printing Bali as many as 30 people, using saturated sampling for all members of the population used as respondents. The analytical tool used to test the hypothesis is multiple linear regression analysis. Based on the analysis results show that communication has a positive and significant effect on employee performance. This means that the better the communication, the better the employee's performance, and vice versa, the lower the communication, the lower the employee's performance. Similarly, work experience has a positive and significant effect on employee performance, this means that if work experience increases, employee performance will increase, otherwise if work experience is decreased, employee performance will decrease.